Pertimbangan Sosiologis Hukum Islam terhadap Penolakan Pornografi di Indonesia: Sociological Considerations of Islamic Law on the Rejection of Pornography in Indonesia - Bakence, Luthfi; Kurniati, Kurniati; Misbahuddin, Misbahuddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
This study aims to determine the sociological considerations of Islamic law against the rejection of pornography in Indonesia. The method and type of research used is descriptive-qualitative research. The results of this study indicate that showing pornography on social media that is easily accessed and watched continuously by someone will have an impact on the rise of adultery, rape, and even murder, as well as various other negative effects. According to Islamic law, pornography is expressly prohibited and is an unlawful act. This can be seen in the Al-Qur'an surah al-Nur/24: 30-31, namely the command to guard the genitals or honor. Likewise in the Al-Qur'an surah al-Isra'/17: 32 regarding the prohibition of approaching adultery and the punishment for adultery in the Al-Qur'an surah al-Nur/24: 2. In Islam, pornography is equated with adultery or serious adultery . Pornographic crimes are not regulated directly by law. Therefore, law is adopted from classical law by adopting law based on existing texts and laws.